OPTIMUM DESIGN FOR CONTROLLING THE SCOURING ON BRIDGE PIERS - Al-Shukur, Abdul-Hassan K.; Ali, Manar Hussein (Salehan Institute of Higher Education, 2019)
The scouring around bridge pier can be considered the most important reasons of bridge failure. Therefore, we investigated by using physical models of piers and we used single pier with square collar , circular collar and interaction of two piers in laboratory channel, its width 1 m and applied three velocities (0.1, 0.08, and 0.07) m/sec. This experimental investigation was made to choose the optimum shape and location of collar of single pier and comparing it with the interaction of two piers, the results showed that both square and circular collar decrease the scour depth, but the square collar is more effective of reducing scouring and the best location at bed level for single pier, comparing the results of single pier with the interaction of two piers, the interaction of two piers without any countermeasure reduced scour depth about 58%.